FRAMEWORK FOR EFFECTIVE COST CONTROL FOR SAFETY COMPLIANCE IN CONSTRUCTION PROJECTS - ANUAR, MOHAMAD ARIF AIMAN (Universiti Teknologi PETRONAS, 2020)
Currently, construction industry is one of the important sector in any development country since it gives big impact in economic growth. However with the obligation of strict safety rules on site, there still an accident happen due to ignorance of human, poor safety practices and lack of knowledge exposure on safety compliance. In order to find the mitigation measure for framework cost control for safety compliance in construction projects in Malaysia, a finding of case study related. Hence this research will reveal the related factor that influences cost of safety compliance in construction industry. The data used in this paper were derived from both primary and secondary sources from literature review. Primary data, it was done through a well-structured questionnaires that distribute to 30 respondents where 83.3% worked less than 5 years in the company among construction industry.